Răspuns :
a) (x-3)(x²+4x+4)-x+3=x^3 +x²-9x-9
b) (x-4)(4x²+4x+1)-x+4=4x^3 -12x²-16x=4x(x²-3x-4)
c) x²+14x+49-25=x²+14x+24
d) x²-12x+36-9x²=-8x²-12x+36=4(-2x²-3x+9)
a)
(x-3)(x+2)²-x+3
x³+4x²+4x-3x²-12x-12-x+3
x³+(4x²-3x²)+(4x-12x-x)+(-12+3)
x³+x²-9x-9
b)
(x-4)(2x+1)²-x+4
4x³+4x²+x-16x²-16x-4-x+4
4x³+(4x²-16x²)+(x-16x-x)+(-4+4)
4x³-12x²-16x
c)
(x+7)²-25
(x+7)²-5²
(x+7-5)(x+7+5)
(x+2)(x+12)
d)
(x-6)²-9x²
(x-6-3x)+(x-6+3x)
(-2x-6)(4x-6)
-4(x+3)(2x-3)
(x-3)(x+2)²-x+3
x³+4x²+4x-3x²-12x-12-x+3
x³+(4x²-3x²)+(4x-12x-x)+(-12+3)
x³+x²-9x-9
b)
(x-4)(2x+1)²-x+4
4x³+4x²+x-16x²-16x-4-x+4
4x³+(4x²-16x²)+(x-16x-x)+(-4+4)
4x³-12x²-16x
c)
(x+7)²-25
(x+7)²-5²
(x+7-5)(x+7+5)
(x+2)(x+12)
d)
(x-6)²-9x²
(x-6-3x)+(x-6+3x)
(-2x-6)(4x-6)
-4(x+3)(2x-3)